PENGEMBANGAN LMS UNTUK MENDUKUNG MULTIPLE INTELLIGENCES BERBASIS PERSONALISASI - Silalahi, Natalia; Bangun, Melly Br.; Ritonga, Rahmilawati (LEARNING : Jurnal Inovasi Penelitian Pendidikan dan Pembelajaran, 2025)
The development of educational technology requires innovation in learning systems that can accommodate the diversity of student characteristics. This study aims to develop and analyze a personalization system in Learning Management Systems (LMS) to support Multiple Intelligences theory for elementary school children through digital integration of Teele Inventory for Multiple Intelligences (TIMI). The research method uses a Design and Development Research (DDR) approach with stages of needs analysis, system design using digital TIMI adaptation, prototype development, internal functionality testing, and expert validation. Research subjects involved 2 validators: experts in educational technology and software engineering. The development results showed that the "MeLearn" LMS prototype successfully integrated personalization systems with digital TIMI instruments, obtaining an average expert validation score of 4.1 (appropriate category with minor revisions). Internal functionality testing showed a 96.7% success rate with main features including digital TIMI assessment, personalized dashboards, and adaptive content recommendation systems. The prototype is capable of automatically mapping students' Multiple Intelligence profiles and providing learning material recommendations that match dominant intelligence tendencies. This research contributes to the development of adaptive learning technology that is responsive to the diversity of multiple intelligences of elementary school children, although it still requires empirical validation with end users ABSTRAKPerkembangan teknologi pendidikan menuntut inovasi dalam sistem pembelajaran yang dapat mengakomodasi keberagaman karakteristik peserta didik. Penelitian ini bertujuan mengembangkan dan menganalisis sistem personalisasi dalam Learning Management System (LMS) untuk mendukung teori Multiple Intelligences pada anak sekolah dasar melalui integrasi digital Teele Inventory for Multiple Intelligences (TIMI). Metode penelitian menggunakan pendekatan Design and Development Research (DDR) dengan tahapan analisis kebutuhan, desain sistem menggunakan adaptasi TIMI digital, pengembangan prototipe, uji fungsionalitas internal, dan validasi ahli. Subjek penelitian melibatkan 2 validator ahli teknologi pendidikan dan rekayasa perangkat lunak. Hasil pengembangan menunjukkan bahwa prototipe sistem LMS "MeLearn" berhasil mengintegrasikan sistem personalisasi dengan instrumen TIMI digital, memperoleh skor validasi ahli rata-rata 4,1 (kategori layak dengan revisi minor). Uji fungsionalitas internal menunjukkan tingkat keberhasilan 96,7% dengan fitur utama meliputi penilaian TIMI digital, dashboard personalisasi, dan sistem rekomendasi konten adaptif. Prototipe mampu melakukan pemetaan profil Multiple Intelligences siswa secara otomatis dan memberikan rekomendasi materi pembelajaran yang sesuai dengan kecenderungan kecerdasan dominan. Penelitian ini memberikan kontribusi dalam pengembangan teknologi pembelajaran adaptif yang responsif terhadap keragaman kecerdasan majemuk anak sekolah dasar, meskipun masih memerlukan validasi empiris dengan pengguna akhir.